DMAB에 의한 P형 실리콘 기판 무전해 니켈-붕소 도금 - 김영기(Young-Gi Kim); 박종환(Jong-Whan Park); 이원해(Won-Hae Lee) (Biuletyn Uniejowski, 1991)
In the basic study of selective electroless Ni plating of Si wafers, plating rate and physical properties are investigated to obtain optimum conditions of contact hole filling. Si wafers are excellently activated in the concentration of 0.5M IF, 1mM PdCl2, 2mM EDTA at $70^{°}C$, 90sec. The optimum condition of Ni-B deposition on p-type Si wafers is 0.1M NiSO4, 0.11M Citrate, $70^{°}C$, pH6.8, 8mM DMAB. The main factor in the sheet resistences variation of films is amorphous and on heat treating matrix was transformed into a stable phase (Ni+Ni3B) at $300-400^{°}C$. But pH or DMAB concentration in the plating solution doesn't play role of heat-affected phase change.